Case Report : Pasien Anak Laki -Laki Usia 5 Tahun dengan Bronkopneumonia - Akhlakul Kharimah; Mardiati Mardiati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Bronchopneumonia is a type of pneumonia that affects the bronchi and alveoli, usually starting in the terminal bronchioles. The terminal bronchioles become blocked with mucopurulent exudate forming patches of consolidation in adjacent lobules. 95% of pneumonia cases in children occur in developing countries. According to WHO estimates, the infant mortality rate due to pneumonia in developing countries is 40 out of 1000 live births or around 15-20% per year. A 5-year-old boy was brought to the Emergency Room of Cut Meutia Hospital with complaints of shortness of breath since 3 days before admission accompanied by a cough with phlegm and fever. The results of a physical examination of the thorax found nasal flaring breathing, chest wall retraction, and rhonchi (+/+). Based on laboratory tests, there was an increase in leukocytes, then a chest X-ray showed an impression of infiltration in the perihilar and paracardial. Based on history, physical examination, and supporting examinations, the patient was diagnosed with Bronchopneumonia. Non-medical management is done through bed rest, balanced nutrition, and adequate fluid balance. Then the patient's medical management is in the form of Cefotaxime injection 500 mg/12 hours, symptomatic management and supportive management for the bronchopneumonia..